Vaginal bleeding with multicystic ovaries and a pituitary mass in a child with severe hypothyroidism. - Mohsin, F; Nahar, N; Azad, K; Nahar, J (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2007 Jul;16(2 Suppl):S60-62 The abstract of this article is available on the PubMed website